Anti-spam techniques based on artificial immune system - Tan, Ying 1964- (CRC Press, 2016)
ntroducing research on anti-spam techniques based on the artificial immune system (AIS) to identify and filter spam, this authoritative book provides a centralized source of detailed information on efficient models and algorithms of AIS-based anti-spam techniques